Reaksi Pasar terhadap Pengukuran Kinerja Perusahaan Prospector dan Defender: Bukti Tambahan untuk Periode Setelah Krisis - Saraswati, Erwin; Atmini, Sari (Jurnal Aplikasi Manajemen, 2009)
Miles and Snow devide firm’s strategy into four types, which are prospector, defender, analyzer and reaction, with prospector and defender as the two extremes. The objectives of this research are to empirically examine the differences in accounting performance between prospector and defender firms and the differences in market reaction as well. Accounting performance are measured by earnings before tax, discontinued operation and extraordinary items, sales growth and dividend payout ratio. Market reaction is proxied by cumulative abnormal returns. Sample of this research consists of 60 firms, 33 firms are categorized as prospectors and 27 firms are categorized as defenders. Data of this research are analyzed using Mann-Whitney U test. The results of this research show that there are no differences in earnings before tax, discontinued operation and extraordinary items, sales growth and market reaction between prospector firms and defender firms. On the contrary, this research found that dividend payout ratio of defender firms are higher than dividend payout ratio of prospector firms, as predicted.Keywords: Defender, prospector, financial performance, market reaction